PERILAKU MORAL EKONOMI MASYARAKAT MELAYU SANGGAU KAPUAS - Ismi Lamisatul Salsabilah; Muhammad Basri; Syamsuri Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research was conducted in Kecamatan Kapuas, Sanggau, Kalimantan Barat. Thepurpose was to determine the morality economic behavior of the Sanggau KapuasMalay community seen on imperative criteria, generalization, symmetry, intrinsicmotivation, and internalization processes. The research approach used isphenomenological qualitative research. Ten informants were determined usingsnowball sampling. Techniques of data collection used interviews and directobservation. Research findings are as follows: 1) Imperative criteria shown in localwisdom; (a) Paradje through Tolak Ajong ritual; (b) Marriage customs through SirihKocik and Sirih Bosar deliveries; (c) Kalengkang embroidery for the observance of theuse of motifs; 2) Generalization criteria shown in local wisdom; (a) Paradje heldannually; (b) Marriage customs through Pengarik rituals; (c) Kalengkang embroideryon how artisans promoting clothes; 3) Symmetry criteria shown in local wisdom;(a) Paradje still held during the pandemic; (b) Marriage customs through placesconsideration; (c) Kalengkang embroidery on equal rights of prices clothing; 4)Intrinsic motivation criteria shown in local wisdom; (a) Paradje regarding sellingpermits; (b) Marriage customs through Somah Ta'zim ritual, and 5) Internalizationprocesses demonstrated through paths; (a) Formal education by providing contextualexamples in schools; (b) Formal education by training; (c) Informal education throughparental roles.Keywords: Economy, Malay Society, Moral Behavior